RESEARCH OF THE CORRECTIVE INFLUENCE OF PLANT EXTRACT WITH ANTIDIABETIC PROPERTIES ON THE HISTOLOGICAL STRUCTURE OF RATS PANCREAS WITH TYPE 2 DIABETES - Марчишин, С.М.; Gudz, N.A.; Крицька, Г.А.; Andriyishyn, A.P.; Tverdohlib, N.O. (World of Medicine and Biology, 2018)
Diabetis mellitus is one of the most wide spread modern diseases. Phitotherapy is of great importance in complex treatment of this pathology. In experiments on rats histologic and morphometric research of experimental animals’ pancreas was made in experimental diabetes mellitus after dexamethason injection and introduction of thick plant extract of Jacon root tubers and preparations of comparison – plant officinal collection “Arphazetin” and well-known synthetic hypoglycemic preparation “Methformin”. Morphologic condition of endocrine islets under such circumstances was better saved compared to animals with control diabetes. Large irregular shaped islets with branches were not seen in lobules. There were much more different sized pancreatic islets in specimens. Endocrine cells in them were arranged in cords and uniformly disposed. Central zones of islets were not significantly ravaged, alpha cells here didn’t show signs of active proliferation or degeneration. Beta cells of full value were much better saved. Nuclei of most cells didn’t have distinct features of destruction, hypertrophy or hyperchromy, cytoplasm was homogenous. In some islets, vessels of microcirculatory bed were filled with formed elements. Morphometric research showed all indexes (optic density of pancreatic islets – total amount of them in specimen, profile of islet – amount of beta cells in islet, functional index – relation of beta cells to alpha cells) to be reliably better compared to control pathology and almost identical to that of pancreas of intact animals. In acinar tissue definite changes were not revealed. Exocrine acini were of usual shape and had typical staiment. Like in diabetes control, proliferation of epithelium in some secretory ducts was evident. Intermediate (transitional) cells – similar to both acinocytes and beta cells were found between acini and near secretory ducts. The obtained morphologic and morphometric data showed that biologically active components of thick plant extract of Jacon root tubers significantly reduced diabetogenic effect of dexametason. Destructive and dystrophic changes in endocrine islets were absent or minimal; the amount of cells with full morphological value was distinctly higher. All this improved renewal of quantitive indexes: normal percentage of different sized islets distribution, correlation of islets profile and their perimeter, and generally increases volume and functional activity of pancreatic endocrine apparatus. Due to correcting influence on endocrine pancreas components, thick plant extract of Jacon root tubers has better positive effect compared to medication “Arphazetin” and almost did not concede the drug “Methformin”.
Keywords: thick extract of Jacon root tubers; experimental diabetes mellitus; dexametason; pancreas; endocrine cells; histologic research